Balanced Budget Government Spending in a Small Open Regional Economy - Peter McGregor; Patrizio Lecca; Kim Swales (European Regional Science Association (ERSA), 2012)
Scotland is engaged in a lively and on-going debate on greater fiscal autonomy and independence, which is politically controversial, especially in respect of tax-varying powers. The Scottish Parliament has the power to make a balanced-budget adjustment in public expenditure by varying the basic rate of income tax. While this power has not so far been used, there is considerable pressure further to increase the fiscal powers of the Scottish Government. The object of this paper is to explore and quantify a number of typical balanced-budget government spending shocks. Here we seek to draw on lessons from recent macroeconomic analyses of fiscal policy, but we adapt them to an explicitly regional context. The regional dimension of the analysis is captured through application to a regional economy characterised by: highly open goods markets in which import and export to GDP ratios are much higher than for the national economy; highly open labour markets characterised by the presence of migration and national and regional wage bargaining institutions; financial markets that are perfectly integrated with the national economy with which the region shares a permanently fixed exchange rate. Furthermore, the macroeconomic "closures" of the model are those appropriate to a region, reflecting an institutional structure in which, for example, the system of national transfers moderates the operation of regional adjustment mechanisms. We develop an intertemporal variant of, AMOS, a computable general equilibrium (CGE) model for Scotland to explore the kinds of balanced-budget fiscal expansions that the Scottish Government could pursue. In response to a balanced budget fiscal expansion the model suggests that: an increase in current government purchase in goods and services has negative multiplier effects only if the elasticity of substitution between private and public consumption is high enough to move downward the marginal utility of private consumers; public capital expenditure crowds in consumption and investment but crowding out effects might arise in the short-run if agents are myopic. The distinctive results for public capital expenditure suggest that the current restriction on the composition of Scottish government expenditures is a very significant one.
Keywords: C68; D58; H71; H72; R13; R50; 330; regional computable general equilibrium analysis; fiscal federalism; fiscal policy